Cystatin C may not be a precious predictor for coronary artery disease and its severity: an area of uncertainty - Vakili, Hossein; Mohamadian, Abdollah; Naderian, Mohammadreza; Khaheshi, Isa (Acta Biomedica Atenei Parmensis, 2018)
Background and Aim: Cystatin C, an endogenous indicator for kidney function, may be also an original indicator for coronBackground and Aim: Cystatin C, an endogenous indicator for kidney function, may be also an original indicator for coronary atherosclerosis. In the current study, we intended to assess its role in establishing the existence of coronary artery disease. We also attempted to present the best cut off point for Cystatin C to discriminate coronary disease from normal coronary condition. Methods: 147 consecutive patients who were candidate for coronary angiography were included into the study. Cystatin C was measured using Auto-analyzer system and by Gentian kit with enzyme calorimetric method. Results: The mean level of Cystatin C in the patients with and without coronary artery disease was 0.97±0.51 mg/l and 1.02±0.40 mg/l with no significant difference (p=0.564). In multivariate logistic regression model, the serum level of Cystatin C could not predict coronary artery disease (OR=1.199, 95% CI: 0.531 to 1.706, p=0.662). According to the area under the ROC curve, Cystatin C was not a good indicator to discriminate coronary artery disease from normal coronary condition (AUC=0.465, 95% CI: 0.372 to 0.559, p=0.470). Considering cut of points of 0.85 and 0.94 for Cystatin C, the sensitivity of this test for predicting coronary artery disease in comparison with coronary angiography was 65% and 51%, respectively. In assessing relationship between serum level of Cystatin C and other chemical biomarkers, Cystatin C was only correlated with serum triglyceride level (r=0.207, p=0.012). Conclusions: Cystatin C measurement may not be a suitable predictor for coronary artery disease and severity of the coronary involvement. Future studies with large sample size are necessitated to demarcate distinct role of Cystatin C in coronary artery disease.  ary atherosclerosis. In the current study, we intended to assess its role in establishing the existence of coronary artery disease. We also attempted to present the best cut off point for Cystatin C to discriminate coronary disease from normal coronary condition.Methods: 147 consecutive patients who were candidate for coronary angiography were included into the study. Cystatin C was measured using Auto-analyzer system and by Gentian kit with enzyme calorimetric method. Results: The mean level of Cystatin C in the patients with and without coronary artery disease was 0.97 ± 0.51 mg/l and 1.02 ± 0.40 mg/l with no significant difference (p = 0.564). In multivariate logistic regression model, the serum level of Cystatin C could not predict coronary artery disease (OR = 1.199, 95% CI: 0.531 to 1.706, p = 0.662). According to the area under the ROC curve, Cystatin C was not a good indicator to discriminate coronary artery disease from normal coronary condition (AUC = 0.465, 95%CI: 0.372 to 0.559, p = 0.470). Considering cut of points of 0.85 and 0.94 for Cystatin C, the sensitivity of this test for predicting coronary artery disease in comparison with coronary angiography was 65% and 51%, respectively. In assessing relationship between serum level of Cystatin C and other chemical biomarkers, Cystatin C was only correlated with serum triglyceride level (r = 0.207, p = 0.012).Conclusions: Cystatin C measurement may not be a suitable predictor for coronary artery disease and severity of the coronary involvement. Future studies with large sample size are necessitated to demarcate distinct role of Cystatin C in coronary artery disease.